AKIBAT HUKUM TERHADAP FRANCHISEE YANG MELAKUKAN WANPRESTASI KEPADA FRANCHISOR DALAM PERJANJIAN FRANCHISE - Suarkayasa, Kadek; Dharma Laksana, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2022)
The purpose of this research to find out the extent of a legal consequences for franchise due to default in the franchise agreement, the author uses normative legal research methods and and utilizations near enactment as the object of exploration. Technique used is library research method. Normative legal research includes legal systematic research and comparative law. This can be seen from the Government Regulation the Implementation of Franchise and Civil Law involved in the franchise business agreement,implementation of the franchise agreement both parties in the agreement cannot be implemented because one of the parties does not fulfill/default in franchise agreement, therefore in implementation to franchise agreement, it is wide open to such problems or disputes, therefore there are often defaults on the franchise agreement that must be carried out by the franchisee. The type of default from the franchisee is late paying the establishment fee, completing something that is rejected by the franchisee, making or completing assistance courses of action that are not as per the strategy the establishment understanding framework that has been regulated in the arrangement, not returning the rights franchisee. It’s undeniable in the franchise agreement there is a franchisee who is in default of the substance of the understanding that has been made based on a mutual agreement, which can result in losses for the franchisor.